2014
DOI: 10.18438/b8mk6g
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities are Assessable: Using an Evidence Based Framework to Identify Assessment Opportunities in Library Technology Departments

Abstract: Abstract Objective – This study aimed to identify assessment opportunities and stakeholder connections in an emerging technologies department. Such departments are often overlooked by traditional assessment measures because they do not appear to provide direct support for student learning. Methods – The study consisted of a content analysis of departmental records and of weekly activity journals which were completed by staff in the Emerging Technologies and Services department in a U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Hamasu and Kelly (2017) discussed the use of logic models by the United States of America's National Network of Libraries of Medicine, and they found that logic models assisted the Network in both designing and evaluating programs. Stoddart and Lajoie (2014) used a modified logic model after conducting an internal review of their academic library's emerging technology and services department. Findings from the initial review revealed that the department lacked assessment and impact evidence in key areas such as student engagement and library space use (Stoddart & Lajoie, 2014).…”
Section: Libraries and Logic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamasu and Kelly (2017) discussed the use of logic models by the United States of America's National Network of Libraries of Medicine, and they found that logic models assisted the Network in both designing and evaluating programs. Stoddart and Lajoie (2014) used a modified logic model after conducting an internal review of their academic library's emerging technology and services department. Findings from the initial review revealed that the department lacked assessment and impact evidence in key areas such as student engagement and library space use (Stoddart & Lajoie, 2014).…”
Section: Libraries and Logic Modelsmentioning
confidence: 99%
“…Stoddart and Lajoie (2014) used a modified logic model after conducting an internal review of their academic library's emerging technology and services department. Findings from the initial review revealed that the department lacked assessment and impact evidence in key areas such as student engagement and library space use (Stoddart & Lajoie, 2014). With this knowledge, the authors used a modified logic model to outline their assessment and impact program.…”
Section: Libraries and Logic Modelsmentioning
confidence: 99%
“…To foster an assessment culture, the Assessment Coordinator at the University Library decided to develop and offer a workshop designed for library staff to illustrate the use of a logic model followed by individual consultations. The logic model was chosen as the workshop topic because logic models have been used as a framework in grant proposals (e.g., IMLS), strategic planning (Dubicki, 2011), library assessment (Stoddart & Lajoie, 2014), program evaluation (Markless & Streatfield, 2017), and program intervention (Kletter, Mendelez-Torres, Lilford & Taylor, 2018). Additionally, logic models are an important training topic (e.g., CARLI Counts, 2019).…”
Section: Evidencementioning
confidence: 99%
“…Mining committee reports and other organizational documents may be possible, but it is advisable to think about what the analysis is trying to demonstrate. Stoddart and Lajoie (2014) describe how to use an evidence-based practice framework to help articulate the questions, assemble the evidence, assess the evidence (and later agree on actions and adapt the implementation). Their case study was an emerging technologies and services department that encompassed services such as digital asset management, a friend-finder tool to help study groups and collaboration with external entities on the Oregon explorer data portal.…”
Section: Data Collection Data Analytics and Collaboration For Strategic Planningmentioning
confidence: 99%